The potential of endophytic bacteria to suppress bacterial leaf blight in rice plants (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Rahma H, Nurbailis, Busniah M, Kristina N, Larasati Y. 2021. The potential of endophytic bacteria to suppress bacterial leaf blight in rice plants. Biodiversitas 23: 775-782. Endophytic bacteria are potential as biocontrol agents against bacterial leaf blight (BLB) disease caused by Xanthomonas oryzae pv. oryzae in rice to support sustainable agriculture. This study aimed to select and characterize 22 endophytic bacteria isolated from healthy rice, determine their ability to promote plant growth and suppress bacterial leaf blight disease in rice and also identify potential endophytic bacterial isolates. The study was arranged in a Completely Randomized Design with 24 treatments and three repetitions. The treatments used in the current study consisted of Xanthomonas oryzae infected plants and treated with endophytic bacterial isolates; infected plants without endophytic bacteria treatment (positive control), non-infected plants (negative control). Identification of potential endophytic bacteria was performed based on 16S rRNA sequences. Three out of 22 bacterial isolates, i.e., LmB1, LmA6, and LmB2 were able to suppress bacterial leaf blight disease with severity levels of 35.82%, 23.78%, and 23.78%, respectively. Based on the rice plant growth parameters, three bacterial isolates (LmA6, LmB1, and LmB35) were able to increase the growth of rice plants with an average value of 69.56%, 56.51%, and 47.82%, respectively. Two bacterial isolates, i.e., LmB 1 and LmA6 suppress the development of bacterial leaf blight disease and increase the growth of rice plants. Based on DNA sequence comparisons of DNA fragments amplified by 16S rRNA related marker of the selected bacterial isolates and database, then LmA6, LmB2, LmB1, and LmB35 had similarities with Bacillus cereus MD152 (96.87%), Bacillus thuringiensis ATCC 10792 (98.20%), Ochrobactrum intermedium strain OI1 (97.52%), and Stenotrophomonas maltophilia strain A1w2 (97.92%), respectively. Our study revealed that the indigenous endophytic bacteria from rice plants could be potential biological agents for controlling bacterial leaf blight disease and increasing plant growth.
Keywords: Biocontrol, endophytic bacteria, sustainable agriculture, Xanthomonas oryzae pv. Oryzae